A survey about the degree of information and awareness of adolescents regarding vaccination in a Province of Central Italy - Fadda, G.; Biasio, L. R.; Mariani, T.; Giambi, C. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Understanding the level of awareness in adolescents on the value of vaccination is kay to developing a proper culture of prevention to counter vaccine hesitancy and the decrease in vaccination coverages. Study design. The aim of the survey was to evaluate awareness, attitudes, opinions, skills and knowledge about vaccines in a group of Italian adolescents through a paper-and-pencil questionnaire. Methods. The questionnaire was administered to adolescents who had appointments in two vaccination centers of the Public Health Authority of Latina (Latium, Italy), between August 2018 and January 2019. Results. In total, 391 forms were completed by teenagers (median age 16 years, 52% females), Results showed that 53% of participants were not aware of their vaccination status. Knowledge, assessed through questions about vaccines and preventable diseases, was generally poor. However, 89% of adolescents had a positive opinion about vaccinations. Spontaneous searches for vaccine information was low (28.7% had looked for information), despite the medium to high interest expressed. The participants usually sought information on vaccines on generic websites (52.8%) compared to getting information from paediatricians (20.4%) or other physicians (3.7%). However, participants recognized paediatricians/GPs (47%) and schools (46.2%) as the most reliable sources of information. Conclusions. Findings are in agreement with previous published data and can be useful to school and health educators in order to teach adolescents about the value of prevention, providing them with the support necessary to improve their abilities and knowledge.